Themes and variations on piRNA-guided transposon control - Zuzana Loubalova; Parthena Konstantinidou; Astrid D. Haase (Mobile DNA, 2023)
Abstract PIWI-interacting RNAs (piRNAs) are responsible for preventing the movement of transposable elements in germ cells and protect the integrity of germline genomes. In this review, we examine the common elements of piRNA-guided silencing as well as the differences observed between species. We have categorized the mechanisms of piRNA biogenesis and function into modules. Individual PIWI proteins combine these modules in various ways to produce unique PIWI-piRNA pathways, which nevertheless possess the ability to perform conserved functions. This modular model incorporates conserved core mechanisms and accommodates variable co-factors. Adaptability is a hallmark of this RNA-based immune system. We believe that considering the differences in germ cell biology and resident transposons in different organisms is essential for placing the variations observed in piRNA biology into context, while still highlighting the conserved themes that underpin this process.